Analisis risiko produksi ribbed smoked sheet (RSS) di PTPN IX Kebun Balong, Jepara - Rena Mardiyah Budiyono; Wiludjeng Roessali; Wahyu Dyah Prastiwi (AGROINTEK, 2024)
Indonesian rubber plantations have the largest area in the world at 3,776.49 thousand hectares, yet they cannot be the largest producer of natural rubber. PTPN IX Balong is a state-owned company that processes latex into RSS. The production often experiences fluctuations which indicate the production risks faced by the company. The study aimed  to examine the agents of production risk that are considered priorities, as well as effective mitigation strategies to reduce the impact of production risk. The research was conducted from November to December 2022 at PTPN IX Balong, Bumiharjo Village, Keling District, Jepara Regency. The research was a case study method with primary data collected by observation and distributing questionnaires to specific key persons. The secondary data were obtained from RSS production records. Data were analyzed using a quantitative method, namely House of Risk (HOR), to answer research purposes. The results showed that there are 8 priority risk agents that will be mitigated, namely high rainfall, long-tapping and picking-up times, errors made by the officers of the smoke room, broken grinding machine, dirty post-harvest tools, improper latex dilution, an excess dosage of antacid, and late application of ammonia. The mitigation strategy used to minimize the priority risk agent (source) consists of 7 risk mitigation strategies. Tightening inspections at the factory is the top priority to be implemented.